Changes in critical thinking using a blended curriculum in a veterinary gynecology and obstetrics course - Payan-Carreira, Rita (2024)
The Think4Jobs Project aimed to integrate critical thinking (CT) into apprenticeships and courses, focusing on assessing changes in CT skills and dispositions. In the second term of the 2022/23 academic year, in the Gynecology, Andrology, and Obstetrics course within the Veterinary Medicine Master’s Programme at the University of Évora, a CT blended curriculum was developed, engrained in case-based strategies adopting an approach resembling the “think aloud” to support students’ clinical reasoning. This involved three distinct case-based activities requiring students to analyze clinical scenarios, navigate the diagnostic process, weigh hypotheses, determine a diagnosis, plan therapeutic approaches, anticipate responses, and plan follow-up procedures. This chapter presents the differences (gains or losses) in CT skills and dispositions resulting from the strategy. To assess changes, students were requested to complete pre-test and post-test questionnaires combining the short-form of the Critical Thinking Self-Assessment Scale (CTSAS-SF) for skills and the Student-Educator Negotiated Critical Thinking Dispositions Scale (SENCTDS) for dispositions. The questionnaires demonstrated strong internal consistency (Cronbach’s alpha of .969 for CTSAS-SF and .842 for SENCTDS). A paired t-test compared the two questionnaires’ scores, with 22 of the 41 (53.7%) enrolled students completing both questionnaires, four males (18.2%), and 18 females (81.8%); students had an average age of 22 years (SD=1.63; age range=21-27). Analysis revealed a significant positive impact on the integrated CT skills score (p = 0.019), particularly in Evaluation, Inference, and Explanation. While there were no significant changes in the integrated CT dispositions or most dimensions (Reflection, Attentiveness, Open-mindedness, Organization, and Intrinsic Goal Motivation), a significant and moderately sized gain was found in Perseverance (p=0.028; Cohen’s d = 0.502). These findings underscore the efficacy of the implemented strategies in enhancing specific facets of CT skills, emphasizing the potential for targeted interventions to foster the development of critical thinking among students.